Pengaruh Rasio Tepung Biji Kecipir, Tepung Daun Kelor dan Mocaf (Modified Cassava Flour) terhadap Sifat Fisikokimia dan Organoleptik Nugget Nabati - Alamsyah, Ahmad; Apriliyanti, Lia; Rasyda, Riezka Zuhriatika; Saloko, Satrijo (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2024)
Plant-based nuggets can be an alternative for consumers who want to reduce meat consumption or for vegetarians. The purpose of this study was to determine the effect of the ratio of winged bean seed flour, moringa leaf flour, and mocaf (modified cassava flour) on the physicochemical and organoleptic properties of vegetable nuggets. This study used an experimental method with a one-factor Completely Randomized Design (CRD), namely the ratio of winged bean seed flour, moringa leaf flour, and mocaf (0%:0%:50%, 4%:1%:45%, 8%:2%:40%, 12%:3%:35%, 16%:4%:30%, and 20%:5%:25%). Parameters observed included moisture content, protein content, antioxidant activity, texture, color and organoleptic (taste and aroma). Observation data were tested with ANOVA at 5% significance level using Co-Stat software. Treatments that were significantly different were further tested using the Honest Differential Test at the same level. The results showed that the ratio of winged bean seed flour, moringa leaf flour and mocaf gave a significantly different effect on moisture content, protein content, antioxidant activity, texture, color, and organoleptic taste, but gave no significantly different effect on the organoleptic aroma of vegetable nuggets.